2017
DOI: 10.1371/journal.pone.0175994
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the epidermis of the purple quail-like (q-lp) mutant of silkworm, Bombyx mori

Abstract: A new purple quail-like (q-lp) mutant found from the plain silkworm strain 932VR has pigment dots on the epidermis similar to the pigment mutant quail (q). In addition, q-lp mutant larvae are inactive, consume little and grow slowly, with a high death rate and other developmental abnormalities. Pigmentation of the silkworm epidermis consists of melanin, ommochrome and pteridine. Silkworm development is regulated by ecdysone and juvenile hormone. In this study, we performed RNA-Seq on the epidermis of the q-lp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…At the same time, these results are consistent with a reaction‐diffusion model of a morphogen gradient, perhaps one that is already implicated in the formation of spot‐like features in insects . This gradient could also modulate differential chitin expression and scale growth. Further transcriptomic and developmental studies on these interesting weevil 3DPC are sorely needed to address these tantalizing questions.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these results are consistent with a reaction‐diffusion model of a morphogen gradient, perhaps one that is already implicated in the formation of spot‐like features in insects . This gradient could also modulate differential chitin expression and scale growth. Further transcriptomic and developmental studies on these interesting weevil 3DPC are sorely needed to address these tantalizing questions.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, developmental biologists have used ommochromes of butterfly wings to tackle the mechanisms and the diversity of colour patterning (Sekimura & Nijhout, ). Today, ommochromes are also involved in transcriptomic studies of grasshoppers, butterflies, damselflies and spiders (Croucher et al, ; Chauhan et al, ; Connahs, Rhen & Simmons, ; Qiu et al, ; Wang et al, ), as well as in clustered regular interspaced short palindromic repeats/CRISPR‐associated protein 9 (CRISPR/Cas9)‐mediated genome editing (Khan, Reichelt & Heckel, ; Xue et al, ; Zhang & Reed, ). Unfortunately, biochemical knowledge did not keep pace with this increase in functional studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with the widely studied synthesis mechanism of epidermal melanin, the function and synthesis mechanism of ommochrome in the epidermis of insect larvae remains unclear. Studies have revealed that quail (q) and quail-like (q-l P ) are complex pigment mutants that contain melanin, ommochrome, and pteridine, and Bmcardinal is also upregulated in the q and q-l P mutants (Nie et al 2014;Wang et al 2017). Moreover, the absence of Bmcardinal activity results in suppressed red pigmentation around the eyespots of larval epidermis in the p S strain (Osanai- Futahashi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al found that the lack of a low-complexity epidermal protein BmorCPH24 in silkworm causes abnormal markings, which suggests that coloration in silkworm larvae is influenced by cuticular proteins (Xiong et al 2017). Previous transcriptomes analyses have been identified a number of cuticular proteins in the pigmented integument of silkworm strains, including quail (q) (Nie et al 2014), quail-like (q-l p ) (Wang et al 2017), black dilute (bd) (Wu et al 2016), sexcontrolled melanism (sml) (He et al 2016), and the epidermis of larvae and wings of adult in butterfly (Zhang et al 2017), suggesting that cuticular proteins are important for epidermal construction and pigmentation. However, the identified Fig.…”
Section: Discussionmentioning
confidence: 99%